"ASSESSING THE ROLE OF INVASIVE SPECIES IN DISRUPTING LOCAL BIODIVERSITY IN TROPICAL ECOSYSTEMS" (International Journal of Food and Nutritional Sciences, 2023)
Tropical habitats are especially vulnerable to the spread of invasive species because native species there have evolved to survive in very specialised ways. how invading species have a negative impact on tropical environments' biodiversity. Our research into the effects of invasive species on native plant and animal communities is based on a mix of field surveys, ecological monitoring, and statistical analysis. Changes in community composition, resource competition, and ecosystem function are some of the ecological effects of species invasions that we also investigate. the paramount importance of keeping tropical ecosystems and biodiversity intact through the prompt identification, tracking, and control of invasive species. This research sheds light on conservation efforts that aim to lessen the impact of invasions and strengthen tropical ecosystems by elucidating the processes via which invasive species affect local biodiversity.